Palliative treatment for multiple spinal metastasis in patient with ovarian cancer - Rully Hanafi Dahlan; Sevline Estethia Ompusunggu; Muhammad Kusdiansah; Ismail Baselim (Neurologico Spinale Medico Chirurgico, 2019)
Ovarian cancer is the fourth most common type of female cancer and the fifth leading cause of cancer death in women. It is the fourth most common malignancy in women. Management varies depending on the patient condition, so one patient can undergo aggressive decompression and stabilization followed by adjuvant therapy, while others may respond to medication and supportive care. The decision to pursue radical surgical treatment is complex, but the indications are becoming clearer. These include radioresistant tumors, obvious spinal instability, clinically significant neural compression secondary to retropulsed bone or from spinal deformity, intractable pain unresponsive to nonoperative measures, and radiation failure.